Access to Biphenyls by Palladium-Catalyzed Oxidative Coupling of Phenyl Carbamates and Phenols - Truchan, Nadina; Jandl, Christian; Pöthig, Alexander; Breitenlechner, Stefan; Bach, Thorsten (Synthesis, 2019)
The oxidative cross-coupling of phenols (3 equiv) to various substituted phenyl N,N-diethylcarbamates was explored with a variety of substrates. Pd(OAc)2 was employed as the catalyst (20 mol%) and K2S2O8 as the stoichiometric oxidant in trifluoroacetic acid as the solvent (50 °C, 2 h). Carbamates without or with a substituent on the phenyl ring (Me, Ph, Cl, OMe) underwent the reaction unless the phenyl substituent was too strongly electron withdrawing (CN). Cross-coupling occurred exclusively in the ortho position relative to the carbamate group. The regioselectivity at the phenol (ortho or para to hydroxy) was mainly determined by steric factors. Yields up to 60–70% were achieved for specific carbamate/phenol combinations.
Keywords: biaryls; carbamates; C-H activation; cross-coupling; oxidation; Pd catalysis.